Human Rights Crisis in Jammu and Kashmir: A Comprehensive Analysis of Systematic Abuses and Urgent Call for Action - Dar, Showkat Ahmad (Journal of Government and Political Issues, 2023)
This manuscript presents a critical analysis of human rights violations in Jammu and Kashmir, aiming to shed light on the gravity of the ongoing crisis. The research focuses on the systematic nature of abuses, including extrajudicial killings, enforced disappearances, torture, sexual violence, and restrictions on freedom of expression and assembly. Employing a descriptive and analytical approach, the study examines the impact of these violations on civilians' lives in the conflict-ridden region, utilizing secondary data sources to provide a comprehensive understanding of the complex human rights situation. The findings reveal alarming statistics, with over 70,000 killings, 8,000 enforced disappearances, and 10,000 cases of torture documented since the insurgency began. Draconian laws like the Armed Forces Special Powers Act (AFSPA) and the Public Safety Act (PSA) have granted security forces immunity, leading to arbitrary detentions and the use of force against civilians. Socio-economic consequences are substantial, with child labor, bonded labor, and forced marriages adding to the challenges. Minority communities, particularly the Muslim community, have faced discriminatory treatment, further exacerbating the crisis. The study emphasizes the urgency of addressing the human rights situation in Jammu and Kashmir, calling for concrete actions from the government and the international community. By highlighting the widespread violations and their impact on various aspects of life, this research urges collective efforts to safeguard the rights and well-being of the people in the region. It contributes to the growing body of knowledge on human rights in Jammu and Kashmir, advocating for justice, peace, and respect for human rights.